Prevention of Fibrosis and Pathological Cardiac Remodeling by Salinomycin. Issue 11 (7th April 2021) - Burke, Ryan M.; Dirkx, Ronald A.; Quijada, Pearl; Lighthouse, Janet K.; Mohan, Amy; O'Brien, Meghann; Wojciechowski, Wojciech; Woeller, Collynn F.; Phipps, Richard P.; Alexis, Jeffrey D.; Ashton, John M.; Small, Eric M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Cardiomyopathy is characterized by the deposition of extracellular matrix by activated resident cardiac fibroblasts called myofibroblasts. There are currently no therapeutic approaches to blunt the development of pathological fibrosis and ventricle chamber stiffening that ultimately leads to heart failure. Objective: We undertook a high-throughput screen to identify small molecule inhibitors of myofibroblast activation that might limit the progression of heart failure. We evaluated the therapeutic efficacy of the polyether ionophore salinomycin in patient-derived cardiac fibroblasts and preclinical mouse models of ischemic and nonischemic heart failure. Methods and Results: Here, we demonstrate that salinomycin displays potent anti-fibrotic activity in cardiac fibroblasts obtained from heart failure patients. In preclinical studies, salinomycin prevents cardiac fibrosis and functional decline in mouse models of ischemic and nonischemic heart disease. Remarkably, interventional treatment with salinomycin attenuates preestablished pathological cardiac remodeling secondary to hypertension and limits scar expansion when administered after a severe myocardial infarction. Mechanistically, salinomycin inhibits cardiac fibroblast activation by preventing p38/MAPK (mitogen activated protein kinase) and Rho signaling. Salinomycin also promotes cardiomyocyte survival and improves coronary vessel density, suggesting that cardioprotection conferred by salinomycin occurs via the integration of multiple mechanisms in multiple relevant cardiac cell types. Conclusions: These data establish salinomycin as an antifibrotic agent that targets multiple cardioprotection pathways, thereby holding promise for the treatment of heart failure patients.